(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, as in all of Bedil’s works, human qualities: respect for man, science and the glory of science, kindness, honesty, hard work, humility, self-discipline, foresight, loyalty, contentment , the description of patience, reflection, and attention is highlighted by analyzing his ghazals, and his role in the education of a well-rounded generation is analyzed.